2018
DOI: 10.3390/microorganisms6040118
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentration of Antibiotics Modulates Gut Microbiota at Different Levels in Pre-Weaning Dairy Calves

Abstract: The aim of this study was to investigate the effect of feeding milk replacer (MR) with two different antibiotics treatments on the gut microbiota of pre-weaning calves. Twelve (12) Holstein male calves at 1-day-old were randomly assigned to: milk replacer without antibiotics (CON), milk replacer plus low cocktail of antibiotics (LCA) concentration (penicillin 0.024 mg/L, streptomycin 0.025 mg/L, tetracycline 0.1 mg/L, ceftiofur 0.33 mg/L), and milk replacer plus a low concentration of single antibiotic (LSA; c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In addition to studies on the rumen, reports on the microbial composition of the feces in dairy calves are abundant. Previous studies have found an association between fecal microbiota and age (Song et al 2018 ), diet (Dill-McFarland et al 2019 ; Wang et al 2019 ), antibiotic therapy (Behr et al 2018 ; Oultram et al 2015 ; Yousif et al 2018 ), and health (Gomez et al 2017 ) in dairy calves. For lactating cows, the core fecal microbiota was identified from ten farms across Northern and Central California, USA (Hagey et al 2019 ).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to studies on the rumen, reports on the microbial composition of the feces in dairy calves are abundant. Previous studies have found an association between fecal microbiota and age (Song et al 2018 ), diet (Dill-McFarland et al 2019 ; Wang et al 2019 ), antibiotic therapy (Behr et al 2018 ; Oultram et al 2015 ; Yousif et al 2018 ), and health (Gomez et al 2017 ) in dairy calves. For lactating cows, the core fecal microbiota was identified from ten farms across Northern and Central California, USA (Hagey et al 2019 ).…”
Section: Introductionmentioning
confidence: 98%
“…Yousif and colleagues investigated the effects of feeding milk replacer both with and without antimicrobials added. The control was unmedicated, while the LCA (“low cocktail of antibiotics”) milk replacer had penicillin (0.024 mg/L), streptomycin (0.025 mg/L), tetracycline (0.1 mg/L) and ceftiofur (0.33 mg/L) added; ceftiofur (0.33 mg/L) was added to the LSA (“low concentration of a single antibiotic”) milk replacer [ 36 ]. The concentrations of antimicrobials added to the milk replacer were based on the authors’ analyses of waste milk on this farm; the median amount was then added to the milk replacer.…”
Section: Discussionmentioning
confidence: 99%
“…The LCA diet significantly reduced ( p = 0.02) the level of Enterobacteriaceae (including E. coli ) found in the intestines compared to the intestines of calves fed unmedicated milk replacer. The authors concluded that feeding a low cocktail of antimicrobials in milk replacer led to a shift in the bacterial taxa of intestinal microbiome, including a reduction in E. coli , which might have a positive effect on calf health by reducing the occurrence of diarrhoea in young calves [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations